The relationship between fatigue severity and mild cognitive impairment in Saudi patients with type 2 diabetes mellitus - Bahgat, Fouad Fathy; Fetyani, Ibrahim Majed; Alnasser, Ali Hamad; Alkhalaf, Abdulmohsen Mohammed; Mohammed Omar Baqais; Habib, Syed Shahid (Journal of the Pakistan Medical Association, 2022)
Type 2 Diabetes Mellitus (T2DM) is a major health issue in Saudi Arabia, with a prevalence of 23.7% in 2015. Several factors contribute to the occurrence of Mild Cognitive Impairment (MCI) and its progression to Alzheimer’s disease in patients with T2DM. This study assesses MCI and fatigue severity and their relationship in patients with T2DM. Out of the 160 Saudi adults interviewed at the King Khalid University Hospital in Riyadh from October 2019 till March 2020, 80 were known cases of T2DM while the rest were non-diabetic individuals. The Montreal Cognitive Assessment (MoCA) test, Mini Mental State Exam (MMSE) and Fatigue Severity Score (FSS) were used to evaluate MCI and fatigue severity, respectively. According to the MoCA scale, 68.7% diabetic individuals as against 42.5% from the non-diabetic group had MCI. While the FSS showed that 40% of the diabetic group vs 26.3% of the non-diabetic were fatigued. In conclusion, patients with T2DM are at a higher risk of developing MCI. Keywords: Type 2 diabetes mellitus, Mild cognitive impairment, Fatigue, Mini mental state exam, Montreal Cognitive Assessment, Saudi Arabia.